DDR1 promotes metastasis of cervical cancer and downstream phosphorylation signal via binding GRB2 - Jin Zhang; Aynuer Maimaiti; Xihan Chang; Pengcheng Sun; Xiaohan Chang (Cell Death and Disease)
Abstract Cervical cancer is a leading cause of cancer-related death among women and its recurrence and metastasis poses challenges to treatment. Discoidin domain receptor 1 (DDR1) was associated with cellular migration and invasion in several types of cancers. However, its function in cervical cancer is still unclear. In this study, we found that DDR1 was significantly more expressed in cervical cancer samples than in normal tissues. SRY-Box transcription factor 2 (SOX2), a known oncogene in cervical cancer, showed a positive correlation with DDR1 and regulated DDR1 transcription, contributing to the elevated expression of DDR1 in cervical cancer. Regarding the function of DDR1 in cervical cancer, the overexpression of DDR1 caused an increase in the migration, invasion, and epithelial-mesenchymal transition (EMT) of cervical cancer cells. In contrast, cervical cancer cells with reduced DDR1 expression exhibited a lower migration rate, fewer invasive cells, and decreased levels of EMT markers. In vivo, mice injected with cervical cancer cells with overexpressed DDR1 showed more pulmonary metastasis and nodule number. Opposite results were found in mice injected with DDR1 silenced cervical cancer cells. Since DDR1 can cause phosphorylation of downstream targets, a phosphorylation omics was employed to reveal the downstream targets of DDR1, including eukaryotic translation initiation factor 4E binding protein 1 and EPH receptor A2. Furthermore, DDR1 bound directly with Src homology 2 domain of growth factor receptor bound protein 2 (GRB2) which mediated the function of DDR1 in the malignant behaviors of cervical cancer and the phosphorylation of downstream targets. In conclusion, DDR1 binds directly to GRB2 and then affects downstream phosphorylation signals, ultimately exacerbating the metastasis of cervical cancer cells. This work sheds light on the mechanism by which DDR1 functions in cervical cancer cells, providing therapeutic strategy for the treatment of cervical cancer.